Efficient and Rapid Solvent-Free Acetylation of Alcohols, Phenols, and Thiols Using Catalytic Amounts of Sodium Acetate Trihydrate - Mohammad M. Mojtahedi; Shamim Samadian (Journal of Chemistry)
Under solvent-free conditions, different alcohols and phenols were efficiently acetylated at room temperature within short time periods by using acetic anhydride in the presence of catalytic quantities of sodium acetate trihydrate, which is a very inexpensive and mild reagent. Thiols were also shown to behave equally well under the same conditions. Chemoselective protection of less hindered alcohols in the presence of bulkier homologues and phenols in the presence of alcohols was achieved using competitive experiments.